Holistic Education in the Formation of Religious Character: A Case Study of Thursina International Islamic Boarding School Malang Junior High School - Haidar, Putri Bayu; Baharuddin, Baharuddin; Syaifuddin, Helmi (AS-SABIQUN, 2025)
Student character problems in the modern era are growing due to globalization, while education still tends to emphasize cognitive aspects alone. Although character building should be central, the implementation of holistic education and integration of divine values remains suboptimal in many schools. This study aims to examine the concept and implementation of holistic education and its implications in the formation of the religious character of students at SMP Thursina International Islamic Boarding School, Malang. The research method uses a qualitative approach with a case study design. Sampling was carried out using purposive sampling, and data were analyzed using the Miles and Huberman model. The results of the study show that the concept of holistic education is stated in the vision and mission of the institution, guided by the Qur'an that humans were created in the best form, so that holistic education is needed. The implementation of holistic education is seen from the integration of six curricula covering religious, academic, and self-development aspects, as well as the instillation of RECODING values ​​(Religious, Caring, Open-minded, Inspiring) inside and outside the classroom. The character-building process is carried out through the habit of worship, teacher role models, the environment, and evaluation through a merit and demerit point system. It has significant implications for students' religious character in daily worship (such as congregational prayer, reading the Qur'an, Sunnah fasting), caring for others, discipline, respecting teachers and friends. This study has implications for becoming a relevant model to be applied in other Islamic educational institutions, especially in the concept of holistic education, integration of divine values ​​in learning and students' daily lives, and evaluation is carried out using a merit and demerit point system to shape students' character.